Desperation in death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel, 2022)
In New York City, 2061, the Pleasure Academy abducts young girls and trains them for a life of sex slavery. Thirteen-year-old Dorian escapes and Dallas tries to expose a sex trafficking ring.